HUBUNGAN IMPLEMENTASI KEBIJAKAN PRAKTEK PROFESIONAL, PENDIDIKAN BERKELANJUTAN, PENGEMBANGAN PROFESI ILMU PENGETAHUAN, DAN PENGABDIAN MASYARAKAT DALAM UPAYA PERPANJANGAN REGISTRASI PERAWAT DENGAN PENINGKATAN KOMPETENSI PERAWAT PPNI KABUPATEN KOTA BANGKALAN - Rahmad Wahyudi (DIA: Jurnal Administrasi Publik, 2016)
Departing from a Policy Implementation Act No. 38 ofÂ  2014 Latest Chapter IV of the registration of nurses , Licensed Practice and Re-registration of the Permits and Implementation of Practice Nurses . Renewal Requirements Competency certificate is nurse must gather Profession Credit Units (SKP) SKP at 25 for 5 years in accordance with the provisions PPNI , SKP obtained through participation activities of Education / Training and Nursing Scientific activities more .This study aimed to explore the relationship of the renewal policy implementation registration of nurses and nurse competence . This research is analytic survey research with cross sectional approach with quantitative approach. with tehnic random sampling (random sampling area). To test the relationship pattern researchers used an analysis tool chi square test. The results showed that : 1) it is connection between the practice of professional nursing with the level of competence, 2) was no relationship between continuing education by the nurse's competence , 3) there is a relationship between the professional development of science with the level of competence, 4) it was relationship between community service with nurse competence.KeywordsÂ  : Nurse Registration Renewal, Professional Practice, Continuing Education, Development Of Science, Community Service, Nurse Competence.